DESIGN OF A STEM-BASED E-MODULE AS A SUSTAINABLE EDUCATION APPROACH TO ENHANCE CRITICAL REASONING SKILLS IN ELEMENTARY SCHOOL - Utaminingsih, Esty Setyo; Qomar, Mohamad Nurul; Wuriningsih, FR.; Idammatussilmi, Idammatussilmi (Universitas Indraprasta PGRI, 2025)
This study aimed to develop and validate a STEAM-based e-module titled “Bersama Selamatkan Keasrian Bumi” (BERSAKSI) to enhance elementary school students' critical reasoning skills within sustainable education. Using the Research and Development (R&D) 4D model-Define, Design, Develop, and Disseminate-the e-module was meticulously crafted and evaluated by experts in content, media, and language, achieving excellent validation ratings (91.6%, 93.7%, and 93.7%, respectively). The module effectively integrated science, technology, engineering, arts, and mathematics to provide a multidisciplinary and interactive learning experience, fostering critical reasoning and ecological awareness. The findings demonstrated alignment with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 13 (Climate Action), by promoting quality education and environmental awareness. While the module demonstrated significant potential in enhancing students' skills and awareness, challenges such as teacher training and infrastructure readiness were identified as critical factors for effective implementation. This research underscores the importance of innovative educational tools in supporting sustainable education and offers a pathway for future studies to explore broader applications and long-term impacts. These findings suggest that the module can inform curriculum design and teacher training for STEAM–SDG integration; however, the evidence is based on expert validation and limited piloting, so broader, longitudinal classroom trials are needed to test its impact and scalability.